Effect of Thermomagnetic Treatment on Structure and Properties of Cu–Al–Mn Alloy - A. N. Titenko; L. D. Demchenko; A. O. Perekos; O. Yu Gerasimov (Nanoscale Research Letters, 2017)
Abstract The paper studies the influence of magnetic field on magnetic and mechanical properties of Cu–Mn–Al alloy under annealing. The comparative analysis of the magnetic field orientation impact on solid solution decomposition processes in a fixed annealing procedure is held using the methods of low-field magnetic susceptibility, specific magnetization, and microhardness test. The paper highlights changes in the magnetic and mechanical properties of Cu–Al–Mn alloy as the result of change in a critical size of forming precipitated ferromagnetic phase and determines correlation in the behavior of magnetic and mechanical properties of the alloy, depending on a critical nucleus size of forming precipitated ferromagnetic phase.